The quest for prosperity : how developing economies can take off - Lin, Justin Yifu, 1952- (Princeton University Press, 2012)
How can developing countries grow their economies? Most answers to this question center on what the rich world should or shouldn't do for the poor world. In The Quest for Prosperity, Justin Yifu Lin--the first non-Westerner to be chief economist of the World Bank--focuses on what developing nations can do to help themselves. Since the end of the Second World War, prescriptions for economic growth have come and gone. Often motivated more by ideology than practicality, these blueprints have had mixed success on the ground. Drawing lessons from history, economic analysis, and pra.
Keywords: Developing countries -- Economic conditions.; Developing countries -- Economic policy.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- General.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Structural Adjustment.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Economics -- General.; Economic history; Economic policy; Developing countries; History & Archaeology.; Business & Economics.; Regions & Countries - Africa.; Economic History.